Estandarización del proceso en la línea de producción de la chiflería “KC” del cantón Chone - Robalino Delgado, Katheryn Valeria (2023)
The objective of this research work was to standardize the process in the production line of green plantain chips of the company KC in Chone, in accordance with the specific requirements for chips such as color, odor, flavor, and characteristic textures according to INEN 2561:2010. A random sampling was carried out to determine the physicochemical properties (moisture, fat, acidity, and peroxide analysis) of the raw material (green plantain), oil and chips. For the development of the research, a diagnosis of control points was carried out by means of a record card and a thermal balance of mass determination that was applied to identify the causes that provoke the softening of the chips, and at the same time implement the same to check the improvements in the control of the production process of the KC chiflería. It was found that the main cause of the softening of green plantain chips is the uncontrolled frying temperature, allowing moisture absorption and rancidity due to lipid oxidation, directly affecting its texture. Finally, it could be seen that there is a significant difference between the means of the percentages of peroxide index in the oil before and after the implementation of the control points